Traditional Chinese architecture : twelve essays - Fu, Xinian (Princeton-China series., 2017)
"Fu Xinian (b. 1933) is considered by many to be the world's leading historian of Chinese architecture. He is an expert on every type of Chinese architecture from every period through the nineteenth century, and his work is at the cutting edge of the field. This wide-ranging book gathers together, for the first time in English, twelve seminal essays by Fu Xinian. It pays special attention to the technical aspects of the building tradition since the first millennium BC, and Fu Xinian's signature drawings abundantly illustrate its nuances. The essays delve into the modular basis for individual structures, complexes, and cities; lateral and longitudinal building frames; the unity of sculpture and building to create viewing angles; the influence of Chinese construction on Japanese architecture; and the reliability of images to inform us about architecture. Organized chronologically, the book also examines such topics as the representation of architecture on vessels in the Warring States period, early Buddhist architecture, and the evolution of imperial architecture from the Tang to Ming dynasty. A biography of Fu Xinian and a detailed Chinese-English glossary are included. Bringing together some of the most groundbreaking scholarship in Chinese architectural history, it showcases an uncontested master of the discipline"--Publisher's description.